The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/cddis.2014.447
|View full text |Cite
|
Sign up to set email alerts
|

A novel antagonist to the inhibitors of apoptosis (IAPs) potentiates cell death in EGFR-overexpressing non-small-cell lung cancer cells

Abstract: In the effort to develop an efficient chemotherapy drug for the treatment of non-small-cell lung cancer (NSCLC), we analyzed the anti-tumorigenic effects of a novel small molecule targeting the inhibitor of apoptosis (IAPs), HM90822B, on NSCLC cells. HM90822B efficiently decreased IAP expression, especially that of XIAP and survivin, in several NSCLC cells. Interestingly, cells overexpressing epidermal growth factor receptor (EGFR) due to the mutations were more sensitive to HM90822B, undergoing cell cycle arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…Several reports indicated that ubiquitous expression of the survivin protein in most malignant cells, but not well-differentiated cells, functions as an inhibitor of the apoptosis protein (IAP, [48]). The survivin gene produces three alternatively spliced variants, including full length, delta Ex3 (∆Ex3), and 2B transcripts (Figure 4, [49]), which exhibit differential effects on the apoptotic process [50].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Several reports indicated that ubiquitous expression of the survivin protein in most malignant cells, but not well-differentiated cells, functions as an inhibitor of the apoptosis protein (IAP, [48]). The survivin gene produces three alternatively spliced variants, including full length, delta Ex3 (∆Ex3), and 2B transcripts (Figure 4, [49]), which exhibit differential effects on the apoptotic process [50].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Although recent studies show the co-overexpression of XIAP and EGFR in many cancers [14, 35, 51, 52], and the high sensitive to anti-IAPs therapy if the cancers with EGFR overexpression [35], a possible association of XIAP with EGFR overexpression has never been explored in previous studies. We demonstrate here that XIAP is a strong positive regulator of EGFR expression in human bladder cancers and that XIAP BIR domain plays an important role in the mediation of EGFR protein expression by promoting its protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is overexpressed in basal-like muscle-invasive bladder cancers, which is sensitive to anti-EGFR therapy [25]. Other studies have shown that EGFR overexpressed tumors are more sensitive to anti-IAPs therapy [35] and XIAP also can lead to the resistance to anti-EGFR therapy [60]. Our studies here found that the overexpression of EGFR was attributed to BIR domain of abnormally expressed XIAP in bladder cancers (BCs), which offers an exciting new opportunity for us to explore the potential usage of XIAP BIR domain as a therapeutic target for invasive BCs, which may avoid the issue of XIAP related anti-EGFR therapy resistance, therefore in turn helping to improve the clinical outcome of patients with invasive BCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are recent notable studies evaluating the relationship between especially response to chemotherapy, EGFR resistance and surviving. [15][16][17][18] In this study, the relationship between survivin in both tumor and metastatic lymph nodes and clinicopathological parameters and survival in patients with squamous cell non-small cell lung cancer, which is more frequently seen in our country were evaluated. The study was approved by the Ethics Committee of Pamukkale University and scientific investigation project.…”
Section: Introductionmentioning
confidence: 99%